PERSPECTIVES AND EXPERIENCES OF INDONESIAN PRE-SERVICE ENGLISH TEACHERS IN DEVELOPING DIGITAL LEARNING RESOURCES - Sudimantara, Lala Bumela (University of Kuningan, 2023)
The adoption of the 2022 Emancipated Curriculum in Indonesia has prompted a need for pre-service English teachers to acquire new skill sets. These skill sets entail the integration of technology and pedagogy, aligning with UNESCO's transformative pedagogy approach to learning, which emphasizes a new paradigm of learning with a focus on essential elements of language learning. This qualitative study aims to investigate the perspectives and experiences of pre-service English teachers in Indonesia in developing digital learning resources for English learners that resonate well with the nature of the Emancipated Curriculum. A phenomenological research approach was adopted, and data were collected through a questionnaire and semi-structured interviews with 16 pre-service English teachers who had completed their final research project on the development of digital learning resources that promote a holistic English language learning. The data was analysed using both corpus analysis and thematic analysis techniques. The findings reveal that pre-service English teachers in Indonesia encounter substantial obstacles when it comes to developing and utilizing digital resources. These challenges include limited access to technology, resistance from schools to embrace digital learning, and students' inadequate English proficiency levels. Despite these constraints, the pre-service teachers generally express satisfaction and confidence in creating their digital learning materials. They also view digital technology as a valuable resource that can enrich the teaching and learning experience. In conclusion, the paper emphasizes the need to equip preservice English teachers in Indonesia with the necessary skills and knowledge to navigate the digital age and work as curriculum engineers effectively. This study suggests that by integrating digital pedagogy and providing access to digital resources, preservice English teachers can become competent curriculum engineers who can deliver quality English language instruction in the 21st century. Ultimately, this will enhance the quality of English language instruction in Indonesia and ensure that preservice teachers are well-prepared to navigate the digital age and provide quality education to their students.